Pengembangan Permainan Simulasi dengan Peragaan (Persiraga) untuk Meningkatkan Pembelajaran Literasi Fisik Jenjang Pendidikan Sekolah Dasar - Arisandi, Rendis Eka; Rosidi, Sakban; Sucipto, Adi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to determine the Development of Simulation Games with Demonstrations (Persiraga) to Improve Physical Literacy Learning at the Elementary School Level. Quantitative study was conducted using causal comparative method by perception comparing between classroom teacher and Physical Education teacher regarding student’s sedentary behaviour in Elementary School in East Java. Data gathered through online questionnaire created with google forms utilizing -points Likert scale, and analyzed using one-sample test and independent-sample test. IBM SPSS Statistics 25 was used to simplify the counting analysis result process. This research findings are: Elementary students’ physical activity does not fulfill the decent criteria according to the classroom teachers, Elementary students’ physical activity does not fulfill the decent criteria according to the Physical Education teachers, and There are no significant perception difference between classroom teachers and Physical Education teachers regarding elementary students’ sedentary behaviour. Keywords: Sedentary behaviour, Screen Time, Classroom teachers’ perception, Physical Education teachers’ perception, Online learning